2014
DOI: 10.1111/his.12543
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian and endometrial endometrioid adenocarcinomas have distinct profiles of microsatellite instability, PTEN expression, and ARID1A expression

Abstract: The different frequencies of molecular genetic alterations between endometrial endometrioid adenocarcinomas and ovarian endometrioid adenocarcinomas imply that distinct processes may be involved in their tumorigenesis or tumour progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 36 publications
4
24
0
1
Order By: Relevance
“…2225 Previous literature indicates that ~41–71% of endometrial cancers and 14–32% of colorectal cancers have a mutation in any exon of PIK3CA . 2629 A modestly higher frequency of PIK3CA mutations has been reported in MSI colorectal cancers compared to MSS cancers, without differentiation by etiology of MSI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2225 Previous literature indicates that ~41–71% of endometrial cancers and 14–32% of colorectal cancers have a mutation in any exon of PIK3CA . 2629 A modestly higher frequency of PIK3CA mutations has been reported in MSI colorectal cancers compared to MSS cancers, without differentiation by etiology of MSI.…”
Section: Discussionmentioning
confidence: 99%
“…We used a selection of Lynch syndrome, MLH1 hypermethylated, and MSS cases for comparison with a large number of double somatic MMR cases. Unlike many prior reports, 22, 24, 42 our analysis was not restricted to certain exons or codons. Even with the relatively small number of cases in this study, we observed multiple significant differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrioidni karcinomi niskog gradusa pokazuju odstupanja u Wnt (engl. Wingless type) signalnom putu koja obuhvaćaju somatske mutacije gena CTNNB1 koji kodira β-catenin, PTEN i PIK3CA 30 . Mucinozni karcinomi u više od 50 % pokazuju KRAS mutaciju 31,32 .…”
Section: Tip 1 Tumoriunclassified
“…A close relationship has been identified between MSI and ARID1A alteration in some neoplasms . SWI/SNF family members such as ARID1A, INI1, BRG1, BRM, BAF155, and BAF170 are involved in the regulation of vital cellular processes, such as proliferation and differentiation, in a wide variety of neoplasms .…”
Section: Introductionmentioning
confidence: 99%